Peningkatan Pengetahuan Petani Jeruk di Kecamatan Gunung Raya Melalui Penyuluhan Penggunaan Pupuk - Firna Varina; Sri Harimurti; Rusnani Rusnani; Sophia Sophia; Ratna Dewi (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Gunung Raya District, Kerinci Regency, has grown to become one of the centers of oranges production in Jambi Province. In general, oranges farmers in Gunung Raya District, use inorganic fertilizers continuously for a long period of time, so that it can cause soil fertility to be disturbed. Counseling on the use of organic and inorganic fertilizers on oranges plants needs to be carried out so that the availability of complete and balanced nutrients in farmland can be maintained, the productivity of oranges did not decrease. With the implementation of this activity, it was hoped that the knowledge of farmers about balanced fertilization on oranges plants and applying it to their farms could increase the production of oranges in Gunung Raya District.